2007
DOI: 10.1093/carcin/bgm074
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensinogen gene polymorphism on Helicobacter pylori infection-related gastric cancer risk in Japanese

Abstract: The carriage of AGT-20 C allele was associated with an increased risk for H.pylori-related gastric cancer development in Japanese, indicating that the RA system plays an important role in the pathogenesis of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 39 publications
1
29
2
Order By: Relevance
“…Previously, the relationship between genes in the renin-angiotensin system and the risk of gastric cancer was investigated (30)(31)(32)(33)(34). One study reported a correlation between the A-20C AGT polymorphism and an increased risk of gastric cancer (34). However, results of our study revealed no association between the AGT M235T polymorphism and gastric cancer risk.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Previously, the relationship between genes in the renin-angiotensin system and the risk of gastric cancer was investigated (30)(31)(32)(33)(34). One study reported a correlation between the A-20C AGT polymorphism and an increased risk of gastric cancer (34). However, results of our study revealed no association between the AGT M235T polymorphism and gastric cancer risk.…”
Section: Discussioncontrasting
confidence: 70%
“…This is the first investigation into a possible correlation between a salt sensitivity gene and gastric carcinogenesis. Previously, the relationship between genes in the renin-angiotensin system and the risk of gastric cancer was investigated (30)(31)(32)(33)(34). One study reported a correlation between the A-20C AGT polymorphism and an increased risk of gastric cancer (34).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several epidemiological and experimental studies have indicated that RAS can influence H. pylori gastritis and the pathogenesis of DU and GAC. 25,26,27,28 Conclusions The present study demonstrates the existence of prominent components of RAS in the human gastric mucosa suggesting local production of angiotensins as well as an Ang II mediated impact on mucosal functions. …”
Section: Figurementioning
confidence: 67%
“…RCC risk in relation to genetic variants in AGT has not been previously studied; however, AGT has been linked with other cancers. Specifically, an increased risk of postmenopausal breast cancer was found in a Dutch population among homozygous carriers of the M allele of rs699 (M235T) (26); a significantly higher number of heterozygote carriers of rs5051 (À6G.A) were found among Czech men with colorectal cancer compared with healthy men of similar age (27), and an increased risk of H. pylori-related gastric cancer was observed in a Japanese population among carriers of the C allele of rs5050 (À20A.C) (28). Rs699 is located in exon 2 and encodes a methionine to threonine amino acid change, and rs5051 and rs5050 are both located in the promoter (Figure 1).…”
Section: Gandreotti Et Almentioning
confidence: 99%